A Bridge to Where? Tracing the Bridge Fuel Metaphor in the Canadian Media Sphere - Chen, Sibo (Frontiers in Communication, 2020)
This paper examines how Canadian media have discussed the role of natural gas in climate change mitigation from 2016 to 2019. It also explicates different stakeholders’ varying stances on the environmental impacts of North America’s ongoing “shale gas boom”, as manifested in their conflicting attitudes toward designating unconventional gas as a bridge to a low-carbon future. The data in question consist of 99 articles published by Canadian media sources, all of which included explicit references to either “bridge fuel” or “transition fuel”. Through a qualitative thematic analysis, I found that more than half of the articles adopted the conventional definition of bridge fuel. Meanwhile, there are three less common, yet noteworthy interpretations arising out of the rest of the articles, which conflict with each other in terms of their views on the relationship between unconventional gas and greenhouse gas emissions reduction. Overall, the fact that bridge fuel references only appeared in a fraction of Canadian environ-mental and energy news reports during the target period suggests the issue’s peripheral status in the Canadian media sphere. Given this situation, the paper ends by calling for more knowledge mobilization efforts to raise public awareness of the controversial factors underlying expanding unconventional gas production and consumption.